A patent review of anticancer glucocorticoid receptor modulators (2014-present). (3rd May 2020) - Lucafò, Marianna; Franzin, Martina; Decorti, Giuliana; Stocco, Gabriele
ABSTRACT: Introduction : Natural and synthetic glucocorticoids are widely employed in different diseases, among which are hematological and solid tumors. Their use is however associated with a number of serious side effects and by the occurrence of resistance. With the aim of separating their gene transactivating effect, more linked to side effects, from transrepressive properties, associated with therapeutic efficacy, a number of selective glucocorticoid modulators have been identified. Areas covered : This review summarizes the patent applications from 2014 to present in the field of selective glucocorticoid receptor modulators employed in cancer therapy. Only few patents have been identified, that concern the identification of new molecules or the method of use of already patented compounds. In addition, a discussion of the mechanism of action of these compounds is included. Expert opinion : Only a very limited number of patents have been applied that concern selective glucocorticoid receptor modulators and their use in cancer. Biological information is scarce for most of these patents; more research is necessary in this field in particular concerning clinical data in order to understand whether it is actually possible to improve the efficacy and therapeutic index of these compounds in cancer therapy.